2020
DOI: 10.1016/j.rmcr.2020.101237
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous tracheostomy in COVID-19 patients: The Miami model

Abstract: The surge in critically ill patients requiring mechanical ventilation fueled by the COVID-19 pandemic has strained healthcare systems globally. With the increasing need for critical care resources, tracheostomy can facilitate weaning from mechanical ventilation and potentially increase availability of critical care resources. In this case series of three patients, we describe our technique for performing bedside percutaneous tracheostomy on patients with persistently positive SARS-CoV-2 real time polymerase ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 7 publications
1
1
0
Order By: Relevance
“…We thus moved to placing Shiley 6 distal XLT tracheostomies as our default device. 13,14 Our median times to tracheostomy (19 d) and times to weaning (17 d) are similar to other reports in the literature. [2][3][4]15,16 Mata-Castro et al 16 found that a longer time from intubation to tracheostomy was related to a longer time from tracheostomy to weaning.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…We thus moved to placing Shiley 6 distal XLT tracheostomies as our default device. 13,14 Our median times to tracheostomy (19 d) and times to weaning (17 d) are similar to other reports in the literature. [2][3][4]15,16 Mata-Castro et al 16 found that a longer time from intubation to tracheostomy was related to a longer time from tracheostomy to weaning.…”
Section: Discussionsupporting
confidence: 88%
“…This may have been because of tracheomalacia from prolonged mechanical ventilation. We thus moved to placing Shiley 6 distal XLT tracheostomies as our default device 13,14…”
Section: Discussionmentioning
confidence: 99%